FUNGSI KOMUNIKASI DALAM TRADISI KETEK COR DI DESA ADAT TEGAL DARMASABA, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Bagus Ade Tegar Prabawa; Made Ika Kusuma Dewi (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2022)
The Ketek Cor tradition is carried out from generation to generation by people in Tegal Darmasaba Traditional Village, Of course, there will be shifts following by times and technology, but the people of the Tegal Darmasaba Traditional Village do not dare to leave there's tradition. The Ketek Cor tradition is a strong necessity so that in the implementation of this tradition there is interaction between people, how was living out of the Tegal Darmasaba Traditional Village with residents who still live in the Tegal Darmasaba Traditional Village. In addition, Ketek Cor tradition can also be a communication link between people's and Ida Sang Hyang Widhi Wasa, this shows that there is harmony between religious and social life in the Tegal Darmasaba Traditional Village community. The results obtained from this study are the cast armpit tradition is full of functions as communicating the meaning of religiosity, the function as communicating the social meaning of society, and the function as communicating economic meaning. From this tradition there is harmony between religious and social life in the Tegal Darmasaba Traditional Village community.